Modelling and Control System Design of Zeta Converter Modification with Coupled Inductor - Capacitor for Seawater Battery Application (Case Study at Indonesian Fishing Boat) - Soedibyo Soedibyo; Mohamad Ridwan; Adam Febranzah; Andri Pradipta (Department of Electrical Engineering ITS and FORTEI, 2017)
Seawater battery is a renewable energy resources that is generated by electrochemical process due to different water salinity. The electromotive force is determined by the number of membrane and ratio of water concentration. In fact, the seawater salinity is variant in ocean. It leads the electromotive force changes in every point (latitude and longitude) on the ocean. This research is presenting: 1) a model of seawater battery which is applied in fishing boat, 2) a design of zeta converter modiffication with coupled inductor and capacitor and PI controller to keep output voltage remain constant.The simulation result verifie the proposed system and control strategyKeywords: renewable energy resources, seawater battery, PI controller, zeta converter, coupled inductor, capasitor.